Determinants of Antihypertensive Medication Adherence among Hemodialysis Patients with Chronic Kidney Disease in Jambi Province, Indonesia - Desti Indri Yani; Ummi Kalsum; Willia Novita Eka Rini; Asparian Asparian; Muldiasman Muldiasman; Armaidi Darmawan (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Chronic kidney disease patients undergoing hemodialysis commonly experience hypertension requiring long-term antihypertensive therapy. Poor medication adherence may increase complications and mortality. Objective: This study aimed to analyze factors associated with antihypertensive medication adherence among chronic kidney disease patients undergoing hemodialysis in Jambi Province, Indonesia. Method: This analytical observational study used a cross-sectional design. A total of 193 respondents were recruited using consecutive sampling. Data were collected using structured questionnaires, including the Morisky Medication Adherence Scale-8 (MMAS-8), knowledge questionnaire, and family support questionnaire. Data were analyzed using univariate, bivariate, and multivariate logistic regression analyses. Results and Discussion: A total of 53.4% of respondents were non-adherent to antihypertensive medication. Bivariate analysis showed no significant association between independent variables and medication adherence (p>0.05). However, knowledge demonstrated a tendency toward association with adherence behavior. Respondents with good knowledge had 2.44 times higher odds of adherence compared with respondents with poor knowledge (Adjusted OR=2.440; 95% CI: 0.887–6.716; p=0.084). Family support remained in the final model as a contributing variable. Conclusion: No statistically significant determinants of antihypertensive medication adherence were identified. However, knowledge and family support showed a tendency to contribute to medication adherence among hemodialysis patients and may be important targets for future interventions